ANALISIS BOD, COD, DAN TSS PADA LIMBAH INDUSTRI MINYAK SAWIT DENGAN METODE FILTRASI MENGGUNAKAN KARBON AKTIF TEMPURUNG BIJI KARET - Ety Jumiati; Abdul Halim Daulay; Siti Rahma Daulay (Universitas Riau, 2022)
This research has carried out the quality of palm oil wastewater before filtration, after filtration, and the most optimal variation. In this study using activated carbon seed shell, zeolite, and silica sand with sample variation A: (60%:20%:20%) , B: (50%:25%:25%), and C: (40% :30%:30%). Tests in this study include: (BOD, COD and TSS). The results of testing the palm oil industrial waste before the filtration process did not meet the RI Minister of Environment Regulation No. 5 tahun 2014, while after the filtration process it met the requirements of the RI Minister of Environment Regulation No. 5 tahun 2014, and the most optimal variation in this test was sample A with value 60% activated carbon.